Strategia zarządzania kapitałem obrotowym brutto a wartość dla akcjonariuszy na przykładzie przemysłu chemicznego - Kowalik, Małgorzata (The Strategy of Gross Working Capital Management and Shareholder Value in Chemical Industry, 2008)
The paper focuses on one of the determinants of shareholder value that is working capital. The strategy of gross working capital management determines the level of working capital and the demand for it. This strategy influences shareholder value creation through the cost of capital and financial result. In the paper, the attempt was made to set the correlation between the applied strategy of gross working capital management and the changes of shareholder value in companies operating in chemical industry.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 332-341